O habitus dos castigos físicos e a Disciplina Positiva na perspectiva de capacitadores níveleducador: construção social do direito da criança a uma educação não punitiva - período de 2003 - 2018 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
This research aims to analyze the perception of Brazilian participants in the Positive Discipline Association at the Educator level in the process of dissemination of the Positive Discipline in the national context and its influence on the habitus of the application of physical punishment as a way of educating the child in the family environment. The Positive Discipline represents an American educational approach developed by Dr. Jane Nelsen, present in more than 60 countries, based on the work of psychologists Alfred Adler and Rudolf Dreikurs. The 'philosophy' of life and strategy assumes that children learn discipline when taught with kindness and firmness at the same time without punishment or rewards. His contribution to education is in the transformation of the adult's gaze on the child, who, before being one, is a developing human being and subject of rights. Law number 13.010 (Boy Bernardo Law), endorsed in 2014, remains unnoticed for most families who continue to be in the habitus of education via physical punishment. This position reveals the complexity with which the subject of punitive education should be investigated, without any Manichean denotation or parental blame for the way they educate their children, but under the focus of understanding the reason for the generational reproduction of this method and the role played by the child in this millenial relationship of domination. Parental empowerment as a social construction and transition phenomenon can be the object of formation and transformation of cultural patterns resulting from the civilizing process, provided that social agents are motivated and encouraged in alternative practices. In order to understand the social space of occurrence of the phenomenon in the social world, the research was conducted by theoretical reflections based on Bourdieu's constructivist structuralism, from its categories of habitus, field and capital. The research is qualitative, carried out on the hypothetical deductive method, with a timeframe from 2003 to 2018. The methodological journey is made by visiting the websites of the Brazilian States, researching the Chamber of Deputies printed newspapers and TV Câmara videos, participating in the Positive Discipline online course, collecting questionnaire responses distributed in two Positive Discipline Workshops and interviews. with Brazilian members registered with the Positive Discipline Association Level Educator as well as research agents. The techniques used correspond to bibliographic, documentary research, simple observation, questionnaire and semi-structured interview. The results confirm the thesis that Positive Discipline is presented as another important instrument of transformation of the way of educating children, and as the other similar methods, with real potential to modify the habitus of punitive education in the family environment. However, the data suggest that the reasons for seeking parental empowerment remain rooted in the traditional adult-centered view. It is not yet a matter of recognizing the right of children, but of solving the problem of parents not losing authority over their children, which explains the persistence and invisibility of the naturalized use of moderate punishment as a way of education, being those behaviours internalized and approved as synonyms of good education.
Keywords: disciplina positiva; parentalidade; castigos físicos; positive discipline; parenting; physical punishment; CNPQ::CIENCIAS SOCIAIS APLICADAS